Perception of School Student Parents under Mid-day Meal Scheme (MDMS) in Paschim Medinipur District of West Bengal, India - Sukanta Biswas, (B.R. Nahata Smriti Sansthan Agricultural Extension Journal (AEXTJ), 2026)
The mid-day meal scheme (MDMS) is one of India’s largest child welfare interventions aimed at reducing classroom hunger and improving educational and nutritional outcomes, particularly among disadvantaged groups. This study examines the perceptions of parents of tribal and non-tribal schoolchildren regarding the implementation and impact of MDMS in Paschim Medinipur district of West Bengal, a region marked by socio-economic vulnerability and significant tribal concentration. Using a purposive-cum-random sampling method, data were collected from parents of 240 students (120 tribal and 120 non-tribal) enrolled in classes V–VIII across four selected schools. A pre-tested semi-structured questionnaire was used, and the data were analyzed through percentages, Kendall’s tau correlation, and constraints ranking. Findings reveal high participation and strong parental satisfaction, particularly among tribal households. Parents widely acknowledged improvements in children’s health, weight, height, nutritional status, activeness, and school attendance. Hygiene in food preparation and regularity of meal service were also positively rated. Correlation analyses demonstrated significant associations between MDMS outcomes and parental socio-demographic characteristics, including education, income, and family type. Despite positive impacts, constraints such as food quality, menu monotony, inadequate cleanliness, and occasional misbehavior during food distribution were reported. Overall, MDMS remains a vital support mechanism, especially for tribal families, enhancing child nutrition, motivation, and school retention.